Awareness towards eye donation among general population: a cross-sectional study from rural Haryana - Manpreet Kaur; Anurag Ambroz Singh; Abhishek Singh (Journal of Integrated Health Sciences)
Introduction: Understanding the reasons why people do or do not donate the eyes is crucial to address the problem of undersupply of cornea and designing any intervention. Aim of this study was to assess the level of awareness towards eye donation and factors influencing among general population residing in the rural area of Haryana state. Methods: We conducted a cross-sectional study during September-December 2014. Patients attending OPD for the purpose of seeking care for their common ailments or diseases formed the study population. Total 360 adults were interviewed using pre-designed and pre-tested questionnaire in local language. Results: Total 76.9% of participants were aware about eye donation. Education, religion and occupation were found to be important predictors for awareness. Sex and age were not significantly associated with awareness. Awareness about eye donation was significantly lower among illiterates (odds ratio 0.14) compared to those who had higher education. Perceived reasons for willingness to donate eyes were pleased to help the blind, doing good to humanity and noble cause. Reasons for unwillingness to donate eyes were, they don't want his/her body to be buried with disfigurement, religion and family permission. Conclusion: Willingness to corneal donation of the studied community is relatively good. This rural population is a good target for mobilization for pledges. Motivators for willingness to donate were the feeling of pleasure in helping the blind and the belief that the act of donation is doing good to humanity, while the dislike to separate the eye from the body after death was the main reason for not being willing to donate.